2018
DOI: 10.1371/journal.pone.0200002
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of mRNAs and lncRNAs involved in cold stress in the wild banana (Musa itinerans)

Abstract: Cold stress seriously affects banana growth, yield and fruit quality. Long noncoding RNAs (lncRNAs) have been demonstrated as key regulators of biotic and abiotic stress in plants, but the identification and prediction of cold responsive mRNAs and lncRNAs in wild banana remains unexplored. In present study, a cold resistant wild banana line from China was used to profile the cold-responsive mRNAs and lncRNAs by RNA-seq under cold stress conditions, i.e. 13°C (critical growth temperature), 4°C (chilling tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 87 publications
1
29
1
Order By: Relevance
“…In recent years, more and more tumor‐associated lncRNAs have been discovered . A large number of published works have reported that these lncRNAs play an important role in multiple tumors . Our previous research shows that lncRNA SNHG17 can promote the proliferation of CRC cells by inhibiting the expression of p57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more tumor‐associated lncRNAs have been discovered . A large number of published works have reported that these lncRNAs play an important role in multiple tumors . Our previous research shows that lncRNA SNHG17 can promote the proliferation of CRC cells by inhibiting the expression of p57 .…”
Section: Discussionmentioning
confidence: 99%
“…18 A large number of published works have reported that these lncRNAs play an important role in multiple tumors. [19][20][21][22][23] Our previous research shows that lncRNA SNHG17…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nta-eTMX27 in Nicotiana tabacum , osa-eTM160 in Oryza sativa (Wang et al, 2017a), lncRNA23468 in Solanum lycopersicum (Jiang et al, 2019), and LTCONS-00042843 in Dimocarpus longan (Chen et al, 2018a) are eTMs that modulate target gene expression by functioning as decoys for relevant miRNAs. The development of high-throughput sequencing and bioinformatics tools enabled the identification of many lncRNAs in several plant species, including model plants like A. thaliana (Yuan et al, 2016), O. sativa (Zhang et al, 2014;Wang et al, 2018a), and Brachypodium distachyon (Quattro et al, 2017), and also in horticultural plants such as S. lycopersicum (Zhu et al, 2015), Cucumis sativus (Hao et al, 2015), Musa itinerans (Liu et al, 2018a), D. longan (Chen et al, 2018a), and Citrus sinensis (Ke et al, 2019). Moreover, lncRNAs in plants help regulate secondary metabolism and stress responses Zhang et al, 2018;Liu et al, 2018a;Wang et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…The development of high-throughput sequencing and bioinformatics tools enabled the identification of many lncRNAs in several plant species, including model plants like A. thaliana (Yuan et al, 2016), O. sativa (Zhang et al, 2014;Wang et al, 2018a), and Brachypodium distachyon (Quattro et al, 2017), and also in horticultural plants such as S. lycopersicum (Zhu et al, 2015), Cucumis sativus (Hao et al, 2015), Musa itinerans (Liu et al, 2018a), D. longan (Chen et al, 2018a), and Citrus sinensis (Ke et al, 2019). Moreover, lncRNAs in plants help regulate secondary metabolism and stress responses Zhang et al, 2018;Liu et al, 2018a;Wang et al, 2019a). However, there has been relatively little research regarding the genome-wide identification and analysis of lncRNAs in tea plants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among the coding-target genes ( Supplementary Table S5) in the pathway of gene expression regulation, we found a set of transcription factors families such as GRAS (targeted by lncRNA_PveLR31442), WRKY (targeted by lncRNA_PveLR32945) and bZIP (targeted by lncRNA_PveLR5534). Genome-wide analysis of lncRNAs in bananas under cold stress revealed that many of lncRNA targets were transcription factor genes, such as MYB, WRKY, bZIP and GRAS transcription factors 77 . Similarly, the co-expression analysis of lncRNAs with transcription factors indicated that the transcription factors related to the WRKY, NAC, MYB and bZIP families were enriched in salt stress condition in wheat 78 .…”
Section: Discussionmentioning
confidence: 99%